Racial differences in time from prostate cancer diagnosis to treatment initiation. Issue 13 (28th May 2013) - Stokes, William A.; Hendrix, Laura H.; Royce, Trevor J.; Allen, Ian M.; Godley, Paul A.; Wang, Andrew Z.; Chen, Ronald C.
<x xml:space="preserve">Abstract</x> BACKGROUND Timely delivery of care has been identified by the Institute of Medicine as an indicator for quality health care, and treatment delay is a potentially modifiable obstacle that can contribute to the disparities among African American (AA) and Caucasian patients in prostate cancer recurrence and mortality. Using the Surveillance, Epidemiologic and End Results (SEER)‐Medicare linked database, we compared time from diagnosis to treatment in AA and Caucasian prostate cancer patients. METHODS A total of 2506 AA and 21, 454 Caucasian patients diagnosed with localized prostate cancer from 2004 through 2007 and treated within 12 months were included. Linear regression was used to assess potential differences in time to treatment between AA and Caucasian patients, after adjusting for sociodemographic and clinical covariates. RESULTS Time from diagnosis to definitive (prostatectomy and radiation) treatment was longer for AA patients in all risk groups, and most pronounced in high‐risk cancer (96 versus 105 days, P < .001). On multivariate analysis, racial differences to any and definitive treatment persisted (β = 7.3 and 7.6, respectively, for AA patients). Delay to definitive treatment was longer in high‐risk (versus low‐risk) disease and in more recent years. CONCLUSIONS AA patients with prostate cancer experienced longer time from diagnosis to treatment than Caucasian patients with prostate cancer. AA patients appear to experience disparities across all aspects of this disease process, and together these factors in receipt of care plausibly contribute to the observed differences in rates of recurrence and mortality among AA and Caucasian patients with prostate cancer. Cancer 2013;119:2486‐2493. © 2013 American Cancer Society.